A novel magnetic microparticles as biocarriers for promoting enrichment of nitrifying bacteria. (June 2022) - Zhang, Fengyuan; Shi, Xiaoshuang; Lian, Shujuan; Chen, Ying; Lu, Mingyi; Feng, Quan; Guo, Rongbo
Abstract: The aim of this research is to enhance enrichment of nitrifying bacteria in activated sludge by adding magnetic microparticles (MMP) as biocarriers. Zeolite powder (ZP) and powdered activated carbon (PAC) were chosen as contrast materials and their effects on nitrifying bacteria enrichment were compared using sequencing batch reactors (SBR). Surface charge and morphology of carriers were analyzed by zeta potential and scanning electron microscopy (SEM) respectively. Results showed that the zeta potential of MMP was 2–50 mV higher than that of ZP and PAC at different pH value. Also, MMP provided a rougher and more porous surface, which was favorable for nitrifying bacteria adhesion. Enrichment system ran for a total of 73 days with five stages. pH value as well as the ammonia nitrogen (NH4 + -N) concentration in daily inflow and outflow of different reactors were compared. MMP-added (R1) and PAC-added (R3) reactors performed better than ZP-added (R2) and the control (R4) in NH4 + -N removal. Additionally, high throughput sequencing result showed that ammonia-oxidizing bacteria (AOB) appeared highest relative abundance of 6.14% with MMP addition after enrichment. Meanwhile, 17 AOB genera coexisted in R1, and only 4, 5 and 4 in R2, R3 and R4 respectively. Overall, these results indicated that MMP was an effective carrier to enhance nitrifying bacteria enrichment. Graphical abstract: Unlabelled Image Highlights: A novel synthetic magnetic micron particle (MMP) was synthesized. MMP promoted nitrifying bacteria enrichment. Addition of MMP facilitated ammonia nitrogen removal efficiency. More different genera of ammonia oxidizing bacteria coexisted with adding MMP.